2010
DOI: 10.3138/cbmh.27.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Nursing History for the Net Generation

Abstract: Abstract. This article describes the development and delivery of an online history of nursing course. The course enables learners to take an in-depth look at the rich and complex history of nursing in Canada and gain an understanding of nurses' influence on society and the contributions nurses have made to building this country, as well as to the health of Canadians. The paper examines the pedagogy of teaching and learning on the web and the implications of a technologically savvy generation of learners. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Studies showed that advocates of nursing history in the curriculum used the opportunity of the reconfiguration of pre-registration education degree and modularised programmes to re-emphasize the importance and create a position for nursing history in undergraduate pre-registration programmes (Kirby, 1998;Lait, 2000;Madsen, 2008;Padilhaa and Nelson, 2009;Buckingham, 2010;Alpern et al, 2011;Toman and Thifault, 2012). Success in this has been limited by a perceived lack of space and lack of agreement surrounding how, why, when and how to teach nursing history.…”
Section: Curriculum Policymentioning
confidence: 93%
See 4 more Smart Citations
“…Studies showed that advocates of nursing history in the curriculum used the opportunity of the reconfiguration of pre-registration education degree and modularised programmes to re-emphasize the importance and create a position for nursing history in undergraduate pre-registration programmes (Kirby, 1998;Lait, 2000;Madsen, 2008;Padilhaa and Nelson, 2009;Buckingham, 2010;Alpern et al, 2011;Toman and Thifault, 2012). Success in this has been limited by a perceived lack of space and lack of agreement surrounding how, why, when and how to teach nursing history.…”
Section: Curriculum Policymentioning
confidence: 93%
“…More recently in the USA, Alpern et al (2011) advocated its inclusion early in the curriculum. Recommendations for nursing history as a stand-alone module while seldom achieved have been universally well supported (Kirby, 1998;Lait, 2000;Buckingham, 2010;Alpern et al, 2011;Toman and Thifault, 2012). With the introduction of the pre-registration nursing diploma programme in the UK, Kirby (1998) placed the subject of nursing history in the first year and made recommendation for the inclusion of further strands in the subsequent second and third undergraduate years.…”
Section: Descriptive Studymentioning
confidence: 97%
See 3 more Smart Citations